Studi Literatur Tentang Perseteruan Antara Yahudi Dengan Samaria Berdasarkan Informasi Yohanes 4:9 - pika idaman jernih hia; Meniati Hia (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2023)
The two groups between Jews and Samaritans are not widely known by Christians in general. The relationship between these two camps has attracted the attention of many people, regarding Jesus' ministry to the Samaritan woman who said: